1987
DOI: 10.1016/0002-9149(87)90984-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability of quantitative digital subtraction coronary angiography before and after percutaneous transluminal coronary angioplasty

Abstract: Quantitative coronary angiography has been proposed as a means of reducing observer variability in the interpretation of coronary angiograms, especially before and after percutaneous transluminal coronary angioplasty (PTCA). Analysis of 13 consecutively acquired biplane digital subtraction angiograms before and after PTCA was undertaken to determine intra- and interobserver variability of absolute lesion diameter, relative videodensitometric cross-sectional area, automated percent diameter stenosis and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…16 Similarly, analysis of interobserver variability for stenosis diameter in the human coronary artery showed high reproducibility (r= 0.97, SEE = 0.19 mm). 17 Briefly, the end-diastolic frames of the cineangiograms were projected on a Vanguard viewer that is optically coupled to a video camera. The video signal was digitized onto an ADAC Laboratories (Milpitas, California) digital angiographic computer.…”
Section: Quantitative Coronary Angiographymentioning
confidence: 99%
“…16 Similarly, analysis of interobserver variability for stenosis diameter in the human coronary artery showed high reproducibility (r= 0.97, SEE = 0.19 mm). 17 Briefly, the end-diastolic frames of the cineangiograms were projected on a Vanguard viewer that is optically coupled to a video camera. The video signal was digitized onto an ADAC Laboratories (Milpitas, California) digital angiographic computer.…”
Section: Quantitative Coronary Angiographymentioning
confidence: 99%
“…Periodic diameter variations due to arterial pressure pulsation, however, have received less attention. In most studies, a single end-diastolic frame is selected because vessel motion and time dependency of the arterial diameter is believed to be minimal during this phase of the cardiac cycle (3,(24)(25)(26)(27). However, contrast concentration can be reduced by increased blood flow during diastole and this can reduce the precision of lesion measurement (1 1).…”
Section: Introductionmentioning
confidence: 99%
“…percent area stenosis, diameter of the normal and stenotic segments, and cross-sec tional area of the normal and stenotic seg ments. Other workers [24] have also shown excellent reproducibility for percent area ste nosis using videodensitometric methods. We were able to obtain similarly excellent intraand interobserver correlations for 34 lesions measured at varying time intervals by two dif ferent observers.…”
Section: Discussionmentioning
confidence: 79%
“…Theoretically, these precautions should not be necessary for videodensitomet ric studies, but we [11] and others [24] have shown that measurements of lesions in differ ent projections give widely different results.…”
Section: Discussionmentioning
confidence: 87%